2017
DOI: 10.1101/235184
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Performance of serological antibody tests for bovine tuberculosis in cattle from infected herds in Northern Ireland

Abstract: 1The ability to accurately identify infected hosts is the cornerstone of effective disease control 1 2 and eradication programs. In the case of bovine tuberculosis, caused by infection with the 1 3pathogen Mycobacterium bovis, accurately identifying infected individual animals has been 1 4 challenging as all available tests exhibit less than 100% discriminatory ability. Here we 1 5 assess the utility of three serological tests and assess their performance relative to skin test where one test was used in conjun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Farm practices relating to both the storage and spreading of slurry can increase the risk of a herd bTB incident [6, 93, 95, 183] and the role of slurry in the transmission of bTB has recently been evaluated [184]. M. bovis can persist in slurry for up to 6 months [183, 185] and spreading of slurry after storage for <2 months has been associated with an increased risk of bTB [105].…”
Section: Landscape Climate and Other Environmental Risk Factorsmentioning
confidence: 99%
“…Farm practices relating to both the storage and spreading of slurry can increase the risk of a herd bTB incident [6, 93, 95, 183] and the role of slurry in the transmission of bTB has recently been evaluated [184]. M. bovis can persist in slurry for up to 6 months [183, 185] and spreading of slurry after storage for <2 months has been associated with an increased risk of bTB [105].…”
Section: Landscape Climate and Other Environmental Risk Factorsmentioning
confidence: 99%
“…In contrast, they are resistant to freezing for prolonged periods. Under ordinary temperatures, M. bovis can persist in slurry and soil for at least 6 months [ 25 ]. The high lipids content makes the mycobacteria resistant to several chemicals and disinfectants, but quaternary ammonium compounds, hexachlorophene and chlorhexidine have a bacteriostatic effect while formaldehyde vapor, chlorine compounds, 70% ethanol, hydrogen peroxide, alkaline glutaraldehyde, and 5% phenol have a bactericidal effect [ 23 ].…”
Section: Etiology Of Btbmentioning
confidence: 99%
“…Consequently, manure and slurry should be stored at least 2 months and 6 months, respectively, to reduce risk of infectiousness. Previously, movement of slurry tankers within and between farm was found to be potentially risky for spreading infection over wider ranges [ 76 ]. More recent work from Ireland has indicated that grazing slurry-treated pasture, where slurry was stored for less than two months, was a risk factor for infection [ 71 ].…”
Section: How Might the Environment Become Contaminated By mentioning
confidence: 99%
“…bovis , although it might survive in some parts of the manure [ 114 ]. Slurry would be expected to present a higher risk [ 76 ]. One could argue that a component of such exposure represents indirect infection (inhalation/ingestion) by the faecal-oral route.…”
Section: How Long Can Mtbc Persist In the Environment?mentioning
confidence: 99%